Reading the Bible intertextually - Hays, Richard B. 1948-2025; Alkier, Stefan 1961-; Huizenga, Leroy Andrew 1974- (Waco, Tex. Baylor University Press, 2009)
Reading the Bible Intertextually explores the revisionary hermeneutical practices of the writers of the four gospels. Each of the contributors examines the distinctive ways that the canonical evangelists put a particular "spin" on the story of Jesus through rereading the Old Testament in different ways. In addition, the evangelists' different ways of reading Israel's Scripture are correlated with different visions for the embodied life of the community of Jesus' followers. This is an exciting new reading of the gospels, bringing interdisciplinary and intertextual readings to the texts, articulated by some of the most brilliant New Testament scholars of our time.
Includes bibliographical references and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Textual -- Congresses; Intertextuality in the Bible -- Congresses; Konferenzschrift -- 2004 -- Frankfurt, Main